High-Impact Clinical Studies That Fomented New Developments in Anesthesia: History of Achievements, 1966–2015 - Kissin I (Drug Design, Development and Therapy, 2021)
Igor Kissin The Department of Anesthesiology, Perioperative and Pain Medicine, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USACorrespondence: Igor KissinThe Department of Anesthesiology, Perioperative and Pain Medicine, Brigham and Women’s Hospital, Boston, MA, 02115, USATel +1 617-732-5052Email ikissin@bwh.harvard.eduAbstract: The aim of this work is to identify the most influential initial clinical studies that fomented important developments in anesthesiology over the past 50 years. Studies fomenting new development can be selected using vastly different approaches and, therefore, might provide diverse outcomes. In the present work, two basic aspects of study assessments – the stage of development (eg, generation of idea, preclinical studies, clinical trials) and the method of selection (eg, committee vote, various types of citation analysis, method of finding the invention disclosure) – were chosen according to the following model. The stage of development: the initial clinical studies demonstrating the basic advantage of an innovation for providing anesthesia. The method: a combination of two factors – the study priority in terms of the time of its publication and the degree of its acknowledgement in the form of citation impact; the time of study publication was regarded as a primary factor, but only if the study’s citation count was =/> 20. The initial high-impact studies were selected for 16 drug-related topics (ketamine, isoflurane, etomidate, propofol, midazolam in anesthesia, vecuronium, alfentanil, atracurium, sevoflurane, sufentanil, rocuronium, desflurane, ropivacaine, remifentanil, dexmedetomidine in anesthesia, and sugammadex), and 9 technique-related topics (ultrasound-guided peripheral nerve block, capnography in anesthesia, target-controlled intravenous anesthesia, pulse oximetry in anesthesia, total intravenous anesthesia, transesophageal echocardiography in anesthesia, combined spinal-epidural anesthesia, and bispectral index). Twenty-five studies were designated the first high-impact studies (one for each topic); 16 are drug-related and 9 are technique-related. Half of the first high-impact studies had a citation count of =/> 100, (range: 100 to 555). The citation count of the other half of high-impact studies did not reach the 100-citation threshold (range: 41 to 97). If a selected first high-impact study had a citation count < 100, a next-on-timeline, additional study with citation count =/> 100 was also selected; (range: 100 to 344). The present results show that an initial high-impact clinical study on a new development in anesthesiology can be determined and that related citations usually vary from one hundred to five hundred.Keywords: anesthetic techniques, citation impact, clinical trials, drugs, priority rules, scientometrics